Insecticidal activity of microencapsulated Schinus molle essential oil - Lopez, A. (2014)
Microencapsulation of the Schinus molle Rev L. (Anacardiaceae) leaves essential oil (EO) has been employed to control the release of active ingredients, protecting them from the external environment, with the concurrent improvement of its insecticidal potential on Haematobia irritans. Four microcapsule formulations (EEO1 to EEO4) of S. molle EO were prepared by spray-drying, using a mini spray dryer and gum Arabic/maltodextrin (AG/MDX) as the carrier in different proportions, at a ratio of 4:1 (MDX/AG:EO). Encapsulation efficiency (EE: 96–100%), powder morphology and particle size distribution were analyzed as responses. An interesting correlation was found between EO free and microcapsules (EEO) in the preliminary and comparative studies of stability (at 45 °C) and in the insecticide activity on H. irritans. In fact, a very slow liberation profile of the microencapsulated EO (EEO4) was observed over a period of 366 h (71% of EO retention), as well as a slower time-dependent insecticide effect (32 and 73% of dead flies at 2 and 4 h of exposure time) compared to the free EO (96% of dead flies at 2 h).